Enhanced energy absorption and microstructural studies on hollow glass microsphere filled closed cell aluminum matrix syntactic foam. (April 2023) - Thiyagarajan, Raja; Senthil Kumar, M
The research on lightweight materials for advanced engineering applications attracted the development of metal matrix syntactic foams. The automobile sector has started using Al-based alloys in structural components such as crash-box, underride-guard, fenders, dampers, A, B, and C Pillars. The present study explores the energy absorption behavior; microstructural characterization such as SEM, EDS, and XRD analysis of hollow glass microsphere (HGM) filled aluminum matrix syntactic foam. A380 aluminum alloy reinforced with different volume fractions 10%, 20%, 30%, and 35% of hollow glass microspheres were used in the fabrication of syntactic foam using the stir casting technique. The quasi-static compression test conducted, evaluated the plateau strength, which improved from 284.14 to 341.69 MPa, and energy absorption capacity was observed in the range 139.25–187.92 MJ/m 3 . The plateau strength and energy absorption capacity were improved by 16.82% and 25.89% for the 35 vol.% HGM sample as compared with 10 vol.% HGM filled aluminum matrix syntactic foam. The addition of a calcium thickening agent in the casting process improved the bonding between aluminum and HGM particle and also the homogeneous distribution of HGM. The XRD analysis revealed the chemical reaction that occurred between aluminum and SiO2 that produced the AlSiO2 and Al2 SiO5 interfacial compounds. This reaction tends to collapse the HGM cell wall and fills it with matrix material.